Pixel color-magnitude diagrams of galaxies in the Fornax cluster using S-PLUS images - Escudero, Carlos Gabriel (2021)
Galaxy clusters are the largest gravitationally bound systems in the universe and, as such, play an important role in cosmological studies. An important resource for studying their properties in a statistical manner are homogeneous and large image datasets covering diverse environments. In this sense, the wide-field images (1.4 deg2) obtained by the Southern Photometric Local Universe Survey (S-PLUS) in 12 optical bands, constitute a valuable tool for that type of studies. In this work, we present a photometric analysis of pixel color-magnitude diagrams, corresponding to a sample of 24 galaxies of different morphological types located in the Fornax cluster.